2019
DOI: 10.1016/j.fertnstert.2019.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Long-term cryostorage of semen in a human sperm bank does not affect clinical outcomes

Abstract: Objective: To evaluate the affect of the duration of donor sperm storage on pregnancy success among women undergoing assisted reproduction. Design: Retrospective cross-sectional study. Setting: Sperm bank. Patient(s): A total of 119,558 specimens retrieved using a clinical information database of young adult men who were qualified sperm donors at the Hunan Province Human Sperm Bank of China from 2001 to 2016. Intervention(s): Analysis of semen samples and clinical outcomes after semen use. Main Outcome Measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 20 publications
1
15
0
Order By: Relevance
“…As most male cancer survivors express a wish to become biological parents, Joshua A. Halpern, MD, MS, suggested that every patient be treated as if they will lose their fertility potential and be offered sperm cryopreservation as early as possible before cancer treatment is started [ 41 ]. Decades of data have shown that clinical outcomes are not different between fresh and cryopreserved sperm, with a frozen-thaw survival rate of about 75% [ 42 ]. A formal oncofertility program can help overcome persistent barriers to fertility preservation, at the level of the patient, physician, and system.…”
Section: Conference Session Synopsismentioning
confidence: 99%
“…As most male cancer survivors express a wish to become biological parents, Joshua A. Halpern, MD, MS, suggested that every patient be treated as if they will lose their fertility potential and be offered sperm cryopreservation as early as possible before cancer treatment is started [ 41 ]. Decades of data have shown that clinical outcomes are not different between fresh and cryopreserved sperm, with a frozen-thaw survival rate of about 75% [ 42 ]. A formal oncofertility program can help overcome persistent barriers to fertility preservation, at the level of the patient, physician, and system.…”
Section: Conference Session Synopsismentioning
confidence: 99%
“…Although storage time did not influence pregnancy outcomes in our study, in clinical practice, manipulations, such as repeated opening of the cryo-tank, transportation of specimens or laboratory procedures over time, may influence pregnancy outcomes. It was thought that annual cleaning and registering might decrease the frozen-thawed survival rate of sperm specimens with longer storage times (5-15 years) [31]. The composition of the preimplantation human embryo culture media and its stability during storage varied [32].…”
Section: Total Eventsmentioning
confidence: 99%
“…A large meta-analysis of 801 patients showed a 49% live-birth success rate for those men who chose to use cryopreserved sperm (34). Long-term storage of sperm additionally does not adversely affect live-birth rates, with similar rates noted at 5, 10, and 15 years of cryopreservation (35).…”
Section: Adultmentioning
confidence: 99%